Widespread Recurrence 7 Years after Radical Abdominal Trachelectomy for Early Cervical Adenocarcinoma - M. Coskun Salman; Nejat Ozgul; Kunter Yuce (Hindawi Limited, 2015)
Cervical cancer is the third most common female cancer worldwide and the use of routine screening resulted in earlier stage and younger age at diagnosis. Fertility preservation via radical trachelectomy comes up as an option in such patients. Recent literature reviews confirm the safety of this operation with excellent oncologic outcomes in appropriately chosen patients. However, recurrent disease is likely and a strict follow-up is recommended to detect recurrences at an early stage following radical trachelectomy. In this report, a case who underwent radical trachelectomy and developed widespread recurrences 7 years after initial surgery possibly due to the lack of oncologic follow-up is discussed.